New insights on the 7Be cycle in the ocean. (April 2023) - Grenier, M.; van Beek, P.; Lerner, P.; Sanial, V.; Souhaut, M.; Lagarde, Marion; Marchal, O.; Reyss, J.L.
Abstract: The cosmogenic radionuclide 7 Be has been applied as a tracer of dynamical processes in the upper ocean and of atmospheric deposition of trace elements at the sea surface. These applications usually assume that 7 Be is entirely in the dissolved form, and that scavenging and downward export of 7 Be by settling particles can be neglected. In this work, we explore these assumptions and more generally assess the significance of the 7 Be activity in the particulate fraction, through the generation of vertical profiles of particulate 7 Be in the open ocean. From detailed measurements obtained from low-background gamma spectrometers placed in underground facilities, we report vertical profiles of 7 Be activity in suspended particles ( 7 Bep ) collected in various oceanic regions: the Mediterranean Sea (DYFAMED station), the Indian Sector of the Southern Ocean (station A3-2 from the KEOPS2 cruise), the Sargasso Sea (OFP station), and the subpolar North Atlantic Ocean (GEOVIDE cruise). We find that, in each oceanic region, 7 Bep activities are generally higher in the mixed layer than in the thermocline. They vary in the mixed layer from 3.0 dpm/m 3 at DYFAMED to 33.1 dpm/m 3 at GEOVIDE cross-over station 51/60, i.e., within a range consistent with previous 7 Bep measurements for the open ocean. For the GEOVIDE cruise, the 7 Bep activities measured on different filter types at different depths are corrected for filter offsets derived from multiple 7 Bep measurements at a near-coastal station in the western Mediterranean Sea. We then combine measurements of total 7 Be activity (Shelley et al., 2017) with our measurements of 7 Bep activity to estimate the solid/solution partitioning of 7 Be. On average, the particulate fraction would represent 6% of total 7 Be activity at 5-m water depth ( n = 6), 22% at 20 m ( n = 2) and 9% at 70 m ( n = 3). At GEOVIDE stations, 7 Bep inventories range from 5% to 19% of the total 7 Be inventories. In the Labrador Sea, the measured 7 Bep inventories are lower than the dry 7 Be deposition fluxes estimated from aerosol samples collected during GEOVIDE, suggesting that a significant portion of 7 Bep may be removed by sinking particles. The distribution coefficient K d for 7 Be increases with depth, with log10 K d averaging 5.2 ± 0.1 at 5 m and 6.1 ± 0.1 between 70 and 150 m, suggesting that scavenging of dissolved 7 Be by particles is more pronounced in the thermocline than in the mixed layer when differences in particle concentrations are taken into account. Overall, our study suggests that, at least in some oceanic regions, the removal of 7 Be by marine particles may be significant and that it may need to be considered in applications of 7 Be as a tracer of oceanic processes and atmospheric deposition. Highlights: We present vertical profiles of particulate 7 Be ( 7 Bep ) in the open ocean. 7 Bep activity generally monotonically decreases with depth below the mixed layer. The GEOVIDE 7 Bep fraction range from 2% to 32% of the total 7 Be activity. GEOVIDE 7 Bep inventories range from 5% to 19% of the total 7 Be inventories. Scavenging of 7 Be by suspended particles in the water column may be significant.